Socioeconomic inequality and caries: a systematic review and meta-analysis - Schwendicke, F; Dörfer, C E; Schlattmann, P; Foster Page, L; Thomson, W M; Paris, S (Journal of dental research, 2015)
Dental caries is the most prevalent disease worldwide, with the majority of caries lesions being concentrated in few, often disadvantaged social groups. We aimed to systematically assess current evidence for the association between socioeconomic position (SEP) and caries. We included studies investigating the association between social position (determined by own or parental educational or occupational background, or income) and caries prevalence, experience, or incidence. Risk of bias was assessed using the Newcastle-Ottawa Scale for observational studies. Reported differences between the lowest and highest SEP were assessed and data not missing at random imputed. Random-effects inverse-generic meta-analyses were performed, and subgroup and meta-regression analyses were used to control for possible confounding. Publication bias was assessed via funnel plot analysis and the Egger test. From 5539 screened records, 155 studies with mostly low or moderate quality evaluating a total of 329,798 individuals were included. Studies used various designs, SEP measures, and outcome parameters. Eighty-three studies found at least one measure of caries to be significantly higher in low-SEP compared with high-SEP individuals, while only 3 studies found the opposite. The odds of having any caries lesions or caries experience (decayed missing filled teeth [DMFT]/dmft > 0) were significantly greater in those with low own or parental educational or occupational background or income (between odds ratio [95% confidence interval] = 1.21 [1.03-1.41] and 1.48 [1.34-1.63]. The association between low educational background and having DMFT/dmft > 0 was significantly increased in highly developed countries (R (2) = 1.32 [0.53-2.13]. Publication bias was present but did not significantly affect our estimates. Due to risk of bias in included studies, the available evidence was graded as low or very low. Low SEP is associated with a higher risk of having caries lesions or experience. This association might be stronger in developed countries. Established diagnostic and treatment concepts might not account for the unequal distribution of caries (registered with PROSPERO [CRD42013005947]).